Antidepressant-like Effects of Ginsenoside Rg1 in the Chronic Restraint Stress-induced Rat Model - Jiang Ning; Lv Jing-Wei; Wang Hai-Xia; Huang Hong; Wang Qiong; Chen Shan-Guang; Qu Li-Na; Alberto Carlos Pires Dias; Liu Xin-Min (KeAi Communications Co., Ltd., 2019)
Objective: To investigate the ameliorating effect of ginsenoside Rg1 on the depression-like behaviors induced by chronic restraint stress (CRS) in rats and the underlying mechanisms. Methods: Forty male Wistar rats were divided into 4 groups according to their baseline sucrose preference: control group, model group, and Rg1-treated groups (5 and 10 mg/kg). Except for control group, the groups were exposed to CRS (6 h/day) for 28 days. All drugs were intraperitoneally administered once daily to CRS rats after restraint stress for 14 days. The behavioral tests were carried out via the open field test (OFT), sucrose preference test (SPT), forced swim test (FST), and the Morris water maze (MWM) 4 weeks following CRS induction. The levels of serum corticosterone (CORT) and the activities of the antioxidant defense biomarkers (SOD, MDA and GSH-x) in the prefrontal cortex (PFC) were analyzed using commercial ELISA kits. The levels of the neurotransmitter (5-HT, 5-HIAA, Ach, NE, GABA and Glu) in the PFC were measured by ultra-performance liquid chromatography tandem mass spectrometry. The protein expression of BDNF, Trkb, Bax and Bcl-2 in the PFC was detected by western blotting. Results: Owing to increased sucrose consumption in the SPT, decreased immobility time in the FST, and the improved cognitive performance in MWM, chronic treatment with Ginsenoside Rg1 was found to significantly attenuate depression- like behaviors (anhedonia, behavioral despair and poor spatial memory) in rats. Moreover, CRS exposure caused evident alterations in the levels of the neurotransmitters (5-HT, 5-HIAA, Ach, GABA and Glu) and the activities of the antioxidant defense biomarkers (SOD, MDA and GSH-x) in the PFC and the levels of corticosterone in serum. However, Ginsenoside Rg1 treatment could restore these levels to normal values. Additionally, Ginsenoside Rg1 treatment significantly reverted the decreased expression of BDNF, Trkb and Bcl-2 and the increased expression of Bax in the PFC of CRS rats. Conclusions: Ginsenoside Rg1 could attenuate the CRS-induced depression-like behaviors, in part, by regulating neurotransmitter levels and HPA function, antagonizing oxidative stress and apoptosis, and restoring BDNF-TrkB signaling in PFC. Altogether, our results provide a novel basis regarding the potential therapeutic effects of Rg1 on depression. Keywords: Ginsenosides Rg1, Depression, Chronic restraint stress, Neurotransmitter, Oxidative stress, BDNF